A Special, Strict, Fat-Reduced, and Carbohydrate-Modified Diet Leads to Marked Weight Reduction even in Overweight Adolescents with Prader-Willi Syndrome (PWS) - Walter Bonfig; Kathi Dokoupil; Heinrich Schmidt (The Scientific World Journal)
Hyperphagia is a frequent symptom in patients with Prader-Willi Syndrome (PWS) and results in marked obesity with the risk of metabolic and cardiovascular complications. Previously, we reported that our special diet for PWS patients is effective in the long run, if started early at about 2 years of age. Our objective in this study was to investigate if our special diet is also effective in PWS adolescents who are already overweight. We provided a strict, fat-reduced, and carbohydrate-modified diet, consisting of 10 kcal/cm height, to five adolescents (two female, three male) with PWS. Patients were prospectively followed at our center for 2-6 years. BMI, BMI-SDS, and Weight-for-Height Index were recorded over that period. The special diet was started at a mean age of 16 years (range: 14.1-18.9 years) and initial BMI was 41.3 kg/m2 (range: 32.4-55.5 kg/m2), corresponding to BMI-SDS +3.6 (range: +2.8 to +4.5 SDS). Weight-for-Height Index was 243% (range: 190-339%). After 2 years of the diet, BMI decreased to 33 kg/m2 (range: 26.7-38 kg/m2), as well as BMI-SDS +2.7 (range: 1.7-3.4 SDS) and Weight-for-Height Index to 191% (range: 157-232%); p < 0.01. The special diet was still effective in reducing weight after 4–6 years, with a mean BMI of 30.5 kg/m2 (range: 24.6–34.5 kg/m2) and a mean BMI-SDS of +2.1 (range: 0.7–2.9). We conclude that in a period of 2–6 years, our strict, fat-reduced, and carbohydrate-modified diet, with 10 kcal/cm height, is effective even in adolescents with PWS who are already overweight.